1971
DOI: 10.1083/jcb.49.2.264
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Endoplasmic Reticulum in Hepatocytes

Abstract: The distribution of glucose-6-phosphatase activity in rat hepatocytes during a period of rapid endoplasmic reticulum differentiation (4 days before birth-1 day after birth) was studied by electron microscope cytochemistry . Techniques were devised to insure adequate morphological preservation, retain glucose-6-phosphatase activity, and control some other possible artifacts . At all stages examined the lead phosphate deposited by the cytochemical reaction is localized to the endoplasmic reticulum and the nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
1

Year Published

1972
1972
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(106 citation statements)
references
References 42 publications
5
99
1
1
Order By: Relevance
“…Thus, the glucose-6-phosphate-accessible space appears to constitute only a fraction of the total water space of microsomes, which can theoretically be explained by a steady-state partial equilibration of glucose-6-phosphate across the microsomal membrane or/and by uneven distribution of the glucose-6-phosphatase system in microsomal vesicles. The latter possibility is not entirely consistent, however, with cytochemical ultrastructural evidence for a widespread distribution of glucose-6-phosphatase enzyme activity within liver endoplasmic reticulum in situ (7). In addition, liver microsomal preparations may well contain a (small) proportion of vesicles from membranes other than endoplasmic reticulum and lacking glucose-6-phosphate transporters.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus, the glucose-6-phosphate-accessible space appears to constitute only a fraction of the total water space of microsomes, which can theoretically be explained by a steady-state partial equilibration of glucose-6-phosphate across the microsomal membrane or/and by uneven distribution of the glucose-6-phosphatase system in microsomal vesicles. The latter possibility is not entirely consistent, however, with cytochemical ultrastructural evidence for a widespread distribution of glucose-6-phosphatase enzyme activity within liver endoplasmic reticulum in situ (7). In addition, liver microsomal preparations may well contain a (small) proportion of vesicles from membranes other than endoplasmic reticulum and lacking glucose-6-phosphate transporters.…”
Section: Discussionmentioning
confidence: 67%
“…de Duve et al (3), which mainly derives from the endoplasmic reticulum (ER) membranes (4). The latency of its activity, discovered in early studies (5,6), together with histochemical studies (7) indicated the compartmentation of the enzyme in the ER lumen. Consistent with this, more recent sequence information (8,9) revealed that mammalian glucose-6-phosphatases contain the carboxyl-terminal two-lysine retention motif by which transmembrane proteins are retained in the ER by retrieval from the Golgi (10,11).…”
mentioning
confidence: 99%
“…A blank containing the sample but no AMP was run for each assay. 1 U of enzyme was defined as the activity which releases 1 tzmol of phosphate as Pl per hour at 37~ G6Pase activity was determined using the procedure described by De Duve et al (11) and Swanson (52), with the slight modification introduced by Leskes et al (28). Samples were incubated for 20 min at 37~ and the reaction was stopped by the addition of 15% TCA; two blanks for each sample were always included: one to which TCA was added at zero time, and one from which G6P was omitted.…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…(31) . The current cytochemical interpretation, however, suggests that in the adult rat liver all the ER membranes are G6Pase positive (33).…”
Section: Methods and Recoveriesmentioning
confidence: 85%